CHARACTER BUILDING IN THE APPLICATION OF COLABORATIVE STRATEGIC READING IN READING CLASS - Putu Ayu Paramita Dharmayanti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2019)
ABSTRACT This research used descriptive qualitative design that aimed at describing character education values that were built in the application of Collaborative Strategic Reading. As the focus of this study was third grade university students who took Intermediate Reading lecture in English Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University. The data obtained in this study are qualitative data. The qualitative data were collected by observation, open questionnaire and guided interview. Data were collected by using researcher as the key instrument and some research instruments such as, field note, list of open questionnaire questions, and list of guided interview questions. The result of observation, open questionnaire and guided interview were analyzed descriptively using Interactive Model. The result of the study concluded that directly application of Collaborative Strategic Reading could build some values of character education, such as curiosity, creativity, communicative, responsible, hard work, love reading, discipline, and democratic but indirectly application of Collaborative Strategic Reading could build all values of character education through the moral value inserted in each text read by the reader.